2020
DOI: 10.3390/catal10040364
|View full text |Cite
|
Sign up to set email alerts
|

Atom-economical Synthesis and Characterization of Poly(oxindolidene thienylene vinylene) Based on Aldol Polycondensation Reaction

Abstract: It is known that π-conjugated polymers can be easily synthesized using monomers which possess metals or halogen atoms as well as transition-metal catalysts. However, in the polymer materials synthesized by such reactions, small amounts of halogens and transition-metal-catalysts remain, often negatively affecting their optoelectronic device performances. Herein, we report a new polycondensation method based on the aldol condensation reaction utilizing the intramolecular resonance effect of the anionic monomer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…As the mechanistic understandings have unfolded, the focus in the field perhaps lies in catalyst design to achieve more desirable materials. Another direction that has opened up recently is transition metal-free synthesis of conjugated polymers, which offer a “greener” alternative to current polymerization methods. …”
Section: Discussionmentioning
confidence: 99%
“…As the mechanistic understandings have unfolded, the focus in the field perhaps lies in catalyst design to achieve more desirable materials. Another direction that has opened up recently is transition metal-free synthesis of conjugated polymers, which offer a “greener” alternative to current polymerization methods. …”
Section: Discussionmentioning
confidence: 99%
“…Generally, the Brønsted acids and bases as well as Lewis acids and bases utilized are p ‐toluenesulfonic acid (PTSA), acetic acid, n ‐butyric acid and LiHMDS/12‐crown‐4 [7] . Concurrently, toluene and tetrahydrofuran are the common solvents used during the reaction process [7d,8] . These structures exhibit significant rigidity due to the conjugation of π‐electrons along the carbon backbone.…”
Section: Aldol Condensation and Synthetic Approachmentioning
confidence: 99%
“…successfully synthesized an oxindole‐based polymer known as poly(oxindolidene thienylene vinylene) (POTV, Figure 2b). [7d] Despite having a relatively low molecular weight ( M n =5.3k), POTV, resembling isoindigo (IID)‐like polymers, exhibits a remarkable hole mobility of 2.24×10 −4 cm 2 V −1 s −1 , highlighting the immense potential of oxindole‐based structures as organic semiconductors. Further optimization of the polymerization conditions by switching the base and reaction temperature could potentially lead to the production of POTV with controllable and relatively higher molecular weights, paving the way for its future application as organic semiconductors.…”
Section: Aldol‐condensation‐derived Organic Functional Materialsmentioning
confidence: 99%
“…33,34 Recently, Higashihara et al reported a controlled aldol polymerization of an AB-type monomer. 35 In this study, we focused on conjugated polymers containing azine bonds in their main chains, 36,37 which are formed by the dehydration condensation of dialdehyde monomers and hydrazine without the need for transition-metal catalysts. 38−40 In 2012, Li et al reported the synthesis of an azine-based polymer with a diketopyrrolopyrrole (DPP) skeleton and ambipolar OFET properties with high carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported aldol polycondensation for synthesizing isoindigo-based conjugated polymers without using transition-metal catalysts such as Pd . The metal-free aldol polycondensation gave ladder-like polymers that serve as n-type semiconducting materials in OFETs. , Recently, Higashihara et al reported a controlled aldol polymerization of an AB-type monomer . In this study, we focused on conjugated polymers containing azine bonds in their main chains, , which are formed by the dehydration condensation of dialdehyde monomers and hydrazine without the need for transition-metal catalysts. In 2012, Li et al reported the synthesis of an azine-based polymer with a diketopyrrolopyrrole (DPP) skeleton and ambipolar OFET properties with high carrier mobilities .…”
Section: Introductionmentioning
confidence: 99%